Pengaruh Motivasi Investasi dan Kemajuan Teknologi Terhadap Minat Berinvestasi di Reksadana Syariah Pada Generasi Z Kota Surabaya - Ainiyah, Nur; Indrarini, Rachma (Universitas Negeri Surabaya, 2022)
The growth in net asset value of sharia mutual funds continues to increase, while the amount of funds under management and market share of sharia mutual funds are still smaller than conventional mutual funds, this shows that investment intention in sharia mutual funds is still low. The purpose of this study was to determine effect of investment motivation and technological progress on investment intention in sharia mutual funds in generation Z in Surabaya. The method used in this research is quantitative and data analysis techniques used multiple linear regression. The results of this study reveal that investment motivation partially affects the investent intention in sharia mutual funds in generation Z in the city of Surabaya. Technological advances partially have no effect on the investment intention in sharia mutual funds in generation Z in the city of Surabaya. And simultaneously, investment motivation and technological progress have an influence on investment intention in sharia mutual funds in generation Z in Surabaya.